Total Body Irradiation (TBI) in pediatric patients - Linsenmeier, Claudia; Thoennessen, Daniel; Negretti, Laura; Bourquin, Jean-Pierre; Streller, Tino; Lütolf, Urs Martin; Oertel, Susanne (Strahlentherapie und Onkologie, 2010)
To retrospectively analyze patient characteristics, treatment, and treatment outcome of pediatric patients with hematologicdiseases treated with total body irradiation (TBI) between 1978 and 2006.